The Cognitive Processing of Emotionally Lyrics on You’re Your Own, Kid by Tylor Swift’s Song : A Psycholinguistic Study - Negara, Kanza Ayomi (Maliki Interdisciplinary Journal, 2025)
This study explores the cognitive processing of emotionally charged lyrics in Taylor Swift’s song You’re On Your Own, Kid through a psycholinguistic lens. The research investigates how the lyrics evoke autobiographical memories, support emotional reflection, and influence listeners’ psychological states. Using qualitative analysis, the study reveals that Swift’s narrative lyrics laden with metaphors, personal struggles, and themes of independence trigger deep emotional evaluation and cognitive engagement. The emotional resonance of the song is further enhanced by social media responses, where listeners publicly share their reflections. These findings suggest that popular music can function not only as entertainment but also as a therapeutic and educational tool, fostering self-awareness and social bonding through shared experiences. The study contributes to the understanding of music’s role in psycholinguistic processing and emotional development, particularly among adolescents and young adults.